PENGEMBANGAN DESA WISATA BERBASIS PARTISIPASI MASYARAKAT LOKAL DENGAN MENGGUNAKAN SUSTAINABLE LIVELIHOOD APPROACH (SLA) DI KAMPUNG BLEKOK KABUPATEN SITUBONDO - Vindi Diah Fatika Sari; Jumiati, Aisah; Prianto, Fajar Wahyu; Wiryaningtyas, Dwi Perwitasari (Jurnal Ekuilibrium, 2025)
This study aims to analyze the development of the Kampung Blekok tourism village in Situbondo Regency using the Sustainable Livelihood Approach (SLA). This approach includes five types of capital assets: human capital, natural capital, physical capital, financial capital, and social capital, while also taking into account aspects of vulnerability, institutional structures, and sustainability strategies. The research uses an exploratory qualitative method with data collection techniques including observation, interviews, and documentation. The results show that natural capital has the highest score in the development process, while financial capital remains low. Strengthening strategies through community training, improvement of tourism facilities, and environmental conservation are key to achieving sustainable development in Kampung Blekok.